An analysis of the relevance of material selected from newspapers as a resource of teaching in english as a language courses foreign - Rodríguez González. , Antonieta; Acuña Caicedo. , Roberto; Caicedo Plúa., Christian (Revista Universidad de Guayaquil, 2017)
The aim of this project is to investigate the educational value and relevance of newspaper materials as a source for teaching grammar, vocabulary and reading strategies. The subject of the research is the analysis of the relevance of selected material from newspapers as a teaching resource in English as a foreign language courses. To carry out this research, five newspapers in English were selected: New York Times, Miami Herald, The Guardian, USA today, and The Sun. Additionally, in this project the bibliographic method was applied to collect the information for the theoretical framework, and the analytical and descriptive methods in the rest of the research stages. The applied techniques were note taking, sample selection, interviews and conversations. Additionally, the instruments used were direct observation forms, questionnaires, graphs, among others. After having analyzed a certain number of articles, reports, news and announcements, it is concluded that these can be a valuable tool to teach grammar, vocabulary and reading. Consequently, to achieve effective communication, the proposal focuses on intensive reading, applying interactive strategies designed for advanced level students.
Keywords: relevance; newspapers; English; teaching; learning